Validation of a 'Work Readiness Scale' for health professional (HP) graduates. (4th May 2021) - Syed Aznal, Sharifah Sulaiha; Nadarajah, Vishna Devi V; Kwa, Siew Kim; Seow, Liang Lin; Chong, David WK; Molugulu, Nagashekhara; Khoo, Erwin Jiayuan; Keng, Pei Sin
Abstract: Background: There is a continuing concern about how graduate work readiness (WR) reflects on the success of universities meeting the requirements of employment. This study is to establish a valid and reliable instrument measuring WR in health professions (HP) graduates of medicine, pharmacy and dentistry. Methods: The study from March 2016 to April 2017 was conducted to validate the 'Work Readiness Scale' (WRS; Deakin University) using Principal Component Analysis and Cronbach - α for internal consistency. It was modified to a four-item even-point scale and distributed as an online survey to 335 final year students of the three programs. Results: A reduction from 64 to 53 items provided good internal consistency in all factors: WC 0.85, OA 0.88, SI 0.88 and PC 0.71. The PC domain had the greatest item reduction from 22 to 6, whilst the SI domain increased in items from 8 to 19. These changes may be associated with difference in understanding or interpretation of the items in the SI domain. Conclusion: The modified WRS can be used to evaluate job readiness in HP graduates. However, it needs further refinement and validation in specific educational and employment contexts.